Efficacy, safety and persistence of Ustekinumab versus Infliximab in bionaive patients with moderate to severe Crohn disease patients: a real world experience - Nik Muhamad Affendi, Nik Arsyad; Xin Hui, Khoo; hilmi, ida normiha (2022)
BACKGROUND AND AIM: Ustekinumab was licenced for treatment of moderate to severe Crohn disease (CD) in Malaysia since March 2020 while Infliximab is a well-established treatment for moderate to severe CD. Our objective is to look at real- world data on efficacy, safety and persistence of Ustekinumab versus Infliximab in our population. METHODS: This was a retrospective, single-centre study conducted in a tertiary centre in Malaysia where we recruited all biologic naïve CD patients who were treated with Ustekinumab or Infliximab for at least 3 month duration. Demographic, clinical data and type of biologic therapy used were recorded. Clinical remission at 3-month, 6-month and 1-year were analyst as well as adverse event and persistence of therapy. RESULTS: A total of 73 patients were recruited: 19 from Ustekinumab cohort and 54 from the Infliximab cohort. There were no significant differences in terms of demographics, disease location and behaviour at diagnosis between the two cohort. Clinical remission for Ustekinumab cohort were 63.2%, 63.2% and 73.3% at 3-month, 6-month and 1-year compared to Infliximab cohort 64.8%, 74.1% and 77.8% at 3-month, 6-month and 1-year. 3 (5.5%) patients developed infusion reaction, 1(1.8%) patient developed tuberculosis, 1 (1.8%) patient developed psoriasiform dermatitis, 1 (1.8%) patient developed shingles in Infliximab cohort while no adverse event recorded in Ustekinumab cohort. Persistence was 78.9% and 61.1% for Ustekinumab and Infliximab respectively at 2-year but this was not statistically significant. CONCLUSION: Our early real world data shows that Ustekinumab is efficacious and safe in inducing and maintaining remission of CD and may have a better persistence as compared to Infliximab therapy.